Metabolic effects of signal transduction inhibition in cancer assessed by magnetic resonance spectroscopy - Moestue, Siver Andreas (Mol Oncol, 2011)
Despite huge efforts in development of drugs targeting oncogenic signalling, the number of such drugs entering clinical practice to date remains limited. Rational use of biomarkers for drug candidate selection and early monitoring of response to therapy may accelerate this process. Magnetic resonance spectroscopy (MRS) can be used to assess metabolic effects of drug treatment both in vivo and in vitro, and technological advances are continuously increasing the utility of this non‐invasive method. In this review, we summarise the use of MRS for monitoring the effect of targeted anticancer drugs, and discuss the potential role of MRS in the context of personalised cancer treatment.